Improving the Performance of Direct Bonded Five-Junction Solar Cells by Optimization of AlInP Window Layer - Ge Li; Hongbo Lu; Xinyi Li; Wei Zhang (Photonics, 2022)
It is well-known that the quantum efficiency (QE) of inverted AlGaInP solar cells is less than that of upright ones, and the mechanism has not been well-explained. In this paper, a Si-doped AlInP window layer, compared with an emitter layer, is revealed to be one more important factor that decreases QE. It is noted that the quality of a heavily Si-doped AlInP window layer would decrease and further deteriorate subsequent active layers. An optimization strategy of a Si-doped AlInP window layer is proposed, which proves effective through time-resolved photoluminescence measurements (TRPL) of double heterojunctions. Inverted 2.1 eV AlGaInP solar cells with an improved AlInP window layer are fabricated. A 60 mV Voc increment is achieved with a remarkable enhancement of the fill factor from 0.789 to 0.827. An enhanced QE of 10% to 20% is achieved at short-wavelength and the peak IQE rises from 83.3% to 88.2%, which presents a nearly identical IQE compared with the upright reference. Further optimization in GaAs homojunction sub-cells is performed by introducing an n-GaInP/p-GaAs heterojunction structure, which decreases the recombination loss in the emitter caused by a poor AlInP window layer. The optimized structure significantly improves the Voc of the inverted GaAs-based T-3J solar cells to 3830 mV, boosting the efficiency of SBT five-junction solar cells to 35.61% under AM0 illumination.